Knowledge, Attitude and Practices Regarding Diabetic Foot Care among Diabetic Patients in a Hospital of Rupandehi - Gita Neupane; Sulochana Ghimire; Chanda Sah; Moonu Shrestha; Manju Pandey; Netra Gautam (Journal of Universal College of Medical Sciences, 2024)
INTRODUCTION Diabetes Mellitus is a chronic disease that occurs either when the pancreas does not produce enough insulin or when the body cannot effectively use the insulin it produces. Diabetic foot ulcers are common and are estimated to affect about 15% of all individuals with diabetes during their lifetimes. The objective of the study is to assess the knowledge, attitude and practice regarding diabetic foot care among diabetic patients. MATERIAL AND METHODS Cross sectional descriptive design study was conducted among 384 diabetic patients selected by using purposive sampling technique. Structured interview questionnare was used for data collection for 6 months periods and was analyzed by using descriptive and interferential statistics with Statistical Package for Social Sciences software version 20. RESULTS The ﬁndings of the study revealed that 23.7% had adequate level of knowledge regarding diabetic foot, 96.9% of the respondents had positive attitude regarding diabetic foot care and 39.0% of the respondents had good practice regarding diabetic foot care. CONCLUSION Based on the ﬁndings, it is concluded that more than three fourth (76.3%) of the diabetic patients had inadequate knowledge regarding diabetic foot. Almost cent percent (96.9%) of the diabetic patients had positive attitude towards the diabetic foot care. More than three ﬁfth (61.0%) of the diabetic patients had poor practices regarding diabetic foot care.